From Waste to Innovation: A Circular Economy Approach for Tissue Engineering by Transforming Human Bone Waste into Novel Collagen Membranes - Lorena Gallego; Kimberly Harvey; Marta Pevida; Luis García-Consuegra; Olivia García-Suárez; Álvaro Meana; María Alvarez-Viejo; Luis Junquera (Biomolecules)
The aim of the circular economy is to treat waste as a valuable raw material, reintegrating it into the industrial economy and extending the lifecycle of subsequent products. Efforts to reduce the production of hard-to-recycle waste are becoming increasingly important to manufacturers, not only of consumer goods but also of specialized items that are difficult to manufacture, such as medical supplies, which have now become a priority for the European Union. The purpose of the study is to manufacture a novel human-purified type I collagen membrane from bone remnants typically discarded during the processing of cortico-cancellous bones in tissue banks and to evaluate its mechanical properties and effectiveness in regenerating bone-critical mandibular defects in rabbits. To prepare the novel membrane, cortico-cancellous bone chip samples from a local tissue bank were processed to isolate collagen by demineralization under agitation in HCl, cast into a silicone mold, and air-dried at room temperature and UV irradiation. The average thickness of the four batches analyzed by SEM was 37.3 μm. The average value of Young’s modulus and tensile strength obtained from the specimens was 2.56 GPa and 65.43 Mpa, respectively. The membrane’s efficacy was tested by creating a critical bicortical and bilateral osteoperiosteal defect in rabbit mandibles. The right-side defects were covered with the collagen membrane, while the left-side defects were left untreated as a control. Nine weeks post-surgery, clinical, radiological, and histological analyses demonstrated new bone formation in the treated areas, whereas the control sites showed no bone regeneration. This innovative approach not only contributes to sustainability in healthcare by optimizing biological waste but also exemplifies efficient resource use in line with the circular economy, offering a cost-effective, biocompatible option that could benefit national health systems.